Longitudinal trends of peripheral blood counts in polycythaemia vera and essential thrombocythemia patients in the UK. Issue 3 (29th June 2022) - Carpenter, Lewis; Rockenschaub, Patrick; Hatton, Grace B.; D'Abrantes, Sofia; Sims, Edward; Scott‐Ram, Nicholas; Ducès, Aurélie; Emanuel, Gabrielle; Mead, Adam J.; Drummond, Mark W.; Lipunova, Nadezda
Abstract: There is sparse evidence of how well haematological targets are met in practice for essential thrombocythemia (ET) and polycythaemia vera (PV) patients. Patient data was collected between 2008 and 2020 from two UK NHS Trusts for ET and PV patients. Longitudinal changes in peripheral blood counts, including the proportion of patients meeting peripheral blood count remission, was modelled. Relative risk of cardiovascular‐related events for patients achieving remission within 3‐months was estimated. A total of 620 ET and 429 PV patients were analysed. For high‐risk patients, haematological parameters decreased in the first months of observation then stabilised within normal reference ranges until year 5. Total time spent in peripheral blood count remission was 39.2% for ET and 29.1% for PV. A lower proportion of ET patients reached target platelet counts (48.3%) compared to WBC (79.1%), whilst PV patients were less likely to reach target haematocrit levels (56.9%) compared to platelets (77.3%) or WBC (74.6%). There was no statistically significant association between reaching target blood counts within 3‐months and cardiovascular risk. Complete haematological remission remains a challenging target in managing PV and ET, however this study was unable to show statistically‐significant evidence that this was associated with increased risk of cardiovascular events.